Pengaruh Pendapatan Asli Daerah, Dana Perimbangan Dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten Dan Kota Di Provinsi Jawa Tengah Tahun 2012-2013 - Muhayanah, Fisa Aprilia, Dr. Zulfikar, SE, M.Si (2016)
Performance is the description of the achievement of the implementation of activities in achieving the objectives, vision and mission of an organization. This study aims to investigate whether Regional Income, Balance Fund, and Capital Expenditure affect the financial performance and the City District Government in Central Java province Years 2012-2013. The population used in this study were all district budget realization reports and Cities in Central Java province consists of 29 districts and 6 cities. The research sample was determined by purposive sampling method. The samples used were 61 for 2 years. The hypothesis test uses multiple linear regression analysis. The model results of this study indicate that (1) the original income affect the financial performance and the City District Government in Central Java Province; (2) The Balance Fund does not affect the financial performance and the City District Government in Central Java Province; (3) Capital expenditures affect the financial performance and the City District Government in Central Java Province.